Teachıng commıtment ıssues of unıty of protected lıfe and sustaınable development - Safar, Raziyev; Gulzar, Azadaliyeva (Dunakavics, 2024)
With the help of modern methods, the interest in training is increasing, and this is already bearing fruit in higher education. The learning process is not focused on the memorization of knowledge, but rather on the application of practical work, which is very important in terms of the integration of science and education. The development of presentation skills in seminar classes with modern methods helps to form the soft and hard skills of students. Replacing the traditional view of training with modernity creates conditions for students to have 21st century skills. By conducting a comparative study and reviewing the results, it is shown that as a result of the application of modern teaching methods to the teaching process, assimilation is higher than in lessons conducted with traditional methods. The research was carried out based on the performance of group work, surveys, test tasks, evaluation results, and the results were determined.